Proposed measures to care for talented students in universities in Saudi Arabia - Al-Subaie, Munirah Saud (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to know the proposed concept of caring for gifted students in the universities of the Kingdom of Saudi Arabia and the study used the descriptive approach for a sample of (57) who are interested in caring for gifted students in the Kingdom of Saudi Arabia, and it was random. specific. The study relied on the questionnaire and theoretical analysis to answer the study questions. Average mean and standard deviations were calculated. The study showed that there is a clear lack of talented care in the universities of the Kingdom of Saudi Arabia. And it presents the results of the urgent need for measures that can develop and improve the care of talented students in the universities of the Kingdom of Saudi Arabia. By increasing interest in the category of gifted students and conducting numerous studies and research to increase efforts in their education and improve the quality of their education, and to provide evidence-based programs in all talented student care programs, in addition to providing private partnerships to support talented care programs.